Outcomes of Mitral Valve Replacement in Patients with Ischemic Mitral Insufficiency - Rudenko, S. A.; Fedkiv, S. V.; Potashev, S. V.; IoffeN. О.; Lazoryshynets, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Functional ischemic mitral insufficiency develops in 10–20% of patients with coronary heart disease (CHD) and has significant negative impact on the potential for patient survival. Chronic functional ischemic mitral insufficiency is found in 11–19% of patients undergoing coronary angiography with CHD and in 20–30% of patients undergoing coronary artery bypass grafting. In the period from 2016 to 2017, 49 procedures of mitral valve replacement in conjunction with coronary artery bypass grafting were performed in patients with ischemic mitral insufficiency at the premises of the National Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine. There were 33 (67.3%) men and 16 (32.6%) women in this category of patients. The mean age was 62.8 ± 7.4 years. The overwhelming majority of patients (73.5%) had the history of hypertension. Endocrinologically confirmed diagnosis of diabetes was found in 9 (18.4%) patients. Ejection fraction varied from 20% to 56% with a mean value of 41.2 ± 8.7%. In 61.2% (30) of cases, the patients had three-vessel lesions of the coronary arteries; in 20.4% (10), two coronary arteries were affected; and 18.4% (9) of patients had one coronary artery. Degree II or higher acute heart failure requiring inotropic support for more than 24 hours in the postoperative period occurred in 24.5% (12) cases. Acute cerebrovascular accident was observed in one patient (3.6%). Preoperative severity of condition in patients of this group as well as postoperative complications determined the length of stay in the intensive care unit of 128.3 ± 74.5 hours, and the duration of hospitalization of 11.7 ± 4.4 days. Postoperative mortality after surgical repair of this pathology in our study was 4.1% (2). Mitral valve replacement is an effective surgical method for the treatment of ischemic mitral insufficiency with good direct results when it is impossible to restore the valve competence by means of plasty. The frequency of postoperative complications and mortality rate are due to severe preoperative state of patients.